Profil KH. Bahaudin Nur Salim (Gus Baha) dan Pengaruhnya pada Generasi Milenial - Qowim Musthofa (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2022)
The name was Gus Baha, a familiar greeting KH. Bahauddin Nur Salim is no stranger to Muslims in Indonesia. His popularity on social media is increasing until there are many Muslim communities who become lovers of Gus Baha. This assumption is based on a lot of research and articles that discuss the figure of Gus Baha, there are 2500 articles that mention the name Gus Baha based on searches on google scholar in 2021. In addition, on the Youtube channel, Gus Baha is one of the millennial Kiai who has millions of viewers in 2020.